2010
DOI: 10.4314/bajopas.v3i1.58808
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between canopy width, height and trunk size in some tree species growing in the Savana zone of Nigeria

Abstract: In this study, the relationships between canopy -width, height and trunk size of the following tree species growing in Kano (12 o N, 8.5 -8.7 o E), a town located in the Sudan Savanna Zone of Northern Nigeria were examined: Parkia biglobosa, (Jacq-Benth), Khaya senegalensis (A. Juss), Eucalyptus species, Adansonia digitata (Linn). Cassia siamea (Lam), Azadirachta indica (A. Juss), Delonix regia (Boj, ex Hook) and Acacia nilotica (Linn). Twenty trees of each species ensured to be free from obvious ecological di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…This is possible since photosynthates are regularly translocated to sinks (branches, trunk and roots) for storage from the source (leaves), where they are produced. This relationship has been established for some tree species including Acacia nilotica, Adansonia digitata, Azadirachta indica, Delonix regia, Khaya senegalensis, Parkia biglobosa, and Cassia siamea within the savanna ecosystem of Nigeria (Arzai and Aliyu, 2010). The positive correlation of litter (leaf and twig) biomass with crown radii is an indication that shedding of litter material varies directly with the size of the canopy.…”
Section: Resultsmentioning
confidence: 89%
“…This is possible since photosynthates are regularly translocated to sinks (branches, trunk and roots) for storage from the source (leaves), where they are produced. This relationship has been established for some tree species including Acacia nilotica, Adansonia digitata, Azadirachta indica, Delonix regia, Khaya senegalensis, Parkia biglobosa, and Cassia siamea within the savanna ecosystem of Nigeria (Arzai and Aliyu, 2010). The positive correlation of litter (leaf and twig) biomass with crown radii is an indication that shedding of litter material varies directly with the size of the canopy.…”
Section: Resultsmentioning
confidence: 89%
“…There were large relative error values of 28.5% and 31.2% in plot 1 for the crown diameter derived by using the VWF and IWS methods, respectively. In the case of the VWF method, this error indicates that the linear relationship (Equation (1)) of one independent variable (tree height) might not be sufficient to explain the variations of crown diameter [60,61]. Tree density directly influences the growth rate in the vertical (tree height) and horizontal (crown diameter) directions because it is closely related to the amount of solar radiation penetrating the canopy.…”
Section: Measurement Of Crown Diametermentioning
confidence: 99%
“…These researchers have indicated 20 years as an interval for comparing the measured parameters and giving generalization, but small intervals such as 3 months have not been considered in determining increments of some tree growth parameters. The linear relationship, however, has been found in some tree species between tree height and diameter at breast height, canopy width and diameter at breast height, and between canopy width and tree height [12]. Studies have also shown that the amount of twig growth is closely related to the amount of the root system that is present except for the year following transplanting when the twig growth is influenced by buds formed the year before since the roots and the top of the tree are out of balance such that the roots cannot supply sufficient water and nutrients to the upper portions of the tree for vigorous growth [13].…”
Section: Introductionmentioning
confidence: 97%